A fuzzy-active force based control architecture for characterizing a nonlinear MIMO system / Tengku Luqman Tengku Mohamed - Tengku Mohamed, Tengku Luqman (2016)
This study examines the modelling and control of a twin rotor multi-input multi-output (MIMO) system (TRMS). An intelligent Active Force Control (AFC) scheme is utilised to compensate disturbances that a conventional PID control algorithm alone is unable to due to the system’s highly nonlinear behaviour. Fuzzy logic (FL) is used to estimate intelligently the inertial properties apart from crude approximation method to initiate the AFC effect. The AFC scheme complements the PID controllers acting on the main as well as the tail rotor. It is evident from the simulation studies performed that the inclusion of the intelligent PID-AFCFL scheme produces a more robust controller as compared to the conventional PID as well as crude PID-AFC systems in compensating unwanted internal as well as external disturbances. The intelligent hybrid control algorithm also significantly improves the system overshoot, rise time and settling time apart from its adaptability towards disturbances as compared to its traditional counterpart.